2022
DOI: 10.3389/fimmu.2022.857727
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF1 Negatively Regulates Treponema pallidum-Induced Inflammation in THP-1 Macrophages by Promoting SOCS3 Translation in an m6A-Dependent Manner

Abstract: BackgroundPrevious studies have confirmed that the bacterium Treponema pallidum (TP) or its proteins provide signals to macrophages that induce an inflammatory response; however, little is known about the negative regulation of this macrophage-mediated inflammatory response during syphilis infection or the underlying mechanism. Recent evidence suggests the role of the RNA modification, N6-adenosine methylation (m6A), in regulating the inflammatory response and pathogen-host cell interactions. Therefore, we hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…Outpatient blood pressure testing can provide reference for doctors to diagnose and treat and provide accurate blood pressure data for patients. The economic cost and time cost of self-measurement of blood pressure at home are lower, and self-monitoring of blood pressure by patients outside medical institutions can effectively help hypertensive patients to quickly understand their blood pressure status in the home environment and prompt patients to take corresponding measures in a timely manner [ 11 – 13 ]. Therefore, the study analyzed the relevant factors of hypertension self-testing and the compliance rate of blood pressure detection and control in community outpatient clinics, in order to provide a reference for improving the blood pressure control compliance rate of hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Outpatient blood pressure testing can provide reference for doctors to diagnose and treat and provide accurate blood pressure data for patients. The economic cost and time cost of self-measurement of blood pressure at home are lower, and self-monitoring of blood pressure by patients outside medical institutions can effectively help hypertensive patients to quickly understand their blood pressure status in the home environment and prompt patients to take corresponding measures in a timely manner [ 11 – 13 ]. Therefore, the study analyzed the relevant factors of hypertension self-testing and the compliance rate of blood pressure detection and control in community outpatient clinics, in order to provide a reference for improving the blood pressure control compliance rate of hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…The m6A reader protein YTHDF1 has been proved to be involved in the in ammatory response. It can not only promote the in ammatory response by regulating the translation of P65 or NLRP3 [41,42], but also inhibit the in ammatory response through SOCS3 [43]. Here, YTHDF1 silencing experiments showed that YTHDF1 could inhibit the secretion of in ammatory factors including TNFα, IL-6, IL-1β and NF-κB in vlPAG, suggesting that YTHDF1 may be one of the key factors regulating the in ammatory response of chronic morphine treatments.…”
Section: Discussionmentioning
confidence: 70%
“…Histopathological assessment is a benchmark for assessing pathological signs exhibited in simultaneous study in which the architecture of organs of treated rats was normal, toxicological signs were not present, and matches with vehicle rats architecture, showing harmless findings of ABEE with LD50 value more than 2000 mg/kg. Toxic substances are metabolically changed into harmless substances in the liver, which is the principal area for metabolism ( Harizal et al, 2010 ; Li et al, 2022 ). At initial phase signs in hepatocytes are not understandable because of suitability of liver to revive the injurious tissues ( Salawu et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%